Impact of immediate postpartum insertion of TCu380A on the quantity and duration of lochia discharges in Tanzania - Projestine Selestine Muganyizi; Grasiana Festus Kimario; France John Rwegoshora; Ponsian Patrick Paul; Anita Makins (BMC, 2021)
Abstract Background The insertion of Intrauterine Contraceptive Device (PPIUD) for the purpose of contraception immediately after delivery is becoming popular in countries where the use of IUD for contraception has been extremely low. Since 2015, Tanzania implemented the initiative by the International Federation of Gynecology and Obstetrics (FIGO) to institutionalize PPIUD. As a result of capacity building and information delivery under the initiative, there have been increased uptake of the method. Working in this context, the focus of the study was to generate evidence on the effect of TCu380A IUD on amount and duration of lochia and equip service providers with evidence-based knowledge which can help them in counselling their PPIUD clients. Objective Establish impact of postpartum TCu380A on amount and duration of lochia. Methods A prospective cohort study of delivered women in two teaching hospitals in Tanzania with immediate insertion of TCu380A or without use of postpartum contraception in 2018. TCu380A models; Optima (Injeflex Co. Brazil) and Pregna (Pregna International, Chakan, India) were used. Follow-up was done by weekly calls and examination at 6th week. Lochia was estimated by Likert Scale 0-4 relative to the amount of lochia on the delivery day. An estimated 250 women sample (125 each group) would give 80% power to detect a desired 20% difference in the proportion of women with prolonged lochia discharges among the Exposed and Unexposed groups. Data analysis was by SPSS. Results Two hundred sixty women were analysed, 127 Exposed and 133 Unexposed. Medical complaints were reported by 41 (28.9%) Exposed and 37 Unexposed (27.8%), p = 0.655. Lack of dryness by end of 6th week was to 31 (23.3%) Exposed and 9 (7.1%) Unexposed, p < 0.001. Exposed had higher weekly mean lochia scores throughout with the difference most marked in 5th week (3.556 Versus 2.039, p < 0.001) and 6th week (1.44 Versus 0.449, p<0.001). Conclusion PPIUD is associated with increased amount of lochia and slows progression to dryness within 6 weeks of delivery. The implications of PPIUD clients' needs to be informed about the possibility of delayed dryness of lochia at time of counseling are discussed.